1993
DOI: 10.1139/y93-054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphetamine on the release of excitatory amino acid neurotransmitters in the basal ganglia of the conscious rat

Abstract: The effects of systemic injections of amphetamine sulfate on the release of aspartic acid, glutamic acid, and glutamine were studied using a push-pull perfusion system in the conscious rat. Amphetamine produced a dose-related increase of the extracellular levels of aspartic acid and glutamic acid. The mean time effect of amphetamine was 40 min, followed by a recovery to baseline levels. The mean percentage increase in amino acids released by the highest dose of amphetamine (5 mg/kg) was as follows: Asp, 334.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Since the dopamine receptor blocker is protective for amphetamine induced amino acid neurotransmitters release (Mora and Porras, 1993) and the selective serotonin uptake inhibitor is protective for amphetamine induced 5-HT depletion (Schmidt, 1987), the current study showed amphetamine-induced enhancement in mRNA levels of glutamatergic NMDA receptor subunits may contribute to amphetamine mediated neurotoxic effects. Furthermore, there are similarities between the immediate effects of amphetamine analogue administration and other drugs of abuse.…”
Section: Discussionmentioning
confidence: 77%
“…Since the dopamine receptor blocker is protective for amphetamine induced amino acid neurotransmitters release (Mora and Porras, 1993) and the selective serotonin uptake inhibitor is protective for amphetamine induced 5-HT depletion (Schmidt, 1987), the current study showed amphetamine-induced enhancement in mRNA levels of glutamatergic NMDA receptor subunits may contribute to amphetamine mediated neurotoxic effects. Furthermore, there are similarities between the immediate effects of amphetamine analogue administration and other drugs of abuse.…”
Section: Discussionmentioning
confidence: 77%
“…In fact, vGLUT2-mediated glutamate release from DA neurons has been found to be essential to AMPH-mediated behavioral responses (Birgner et al, 2009). Elevations in extracellular glutamate concentrations after AMPH treatment have been observed in the striatum (Del Arco et al, 1999; Mora and Porras, 1993), nucleus accumbens (Dalia et al, 1998; Xue et al, 1996) and prefrontal cortex (Del Arco et al, 1998) supporting a role for AMPH-mediated EAAT3 modulation at post-synaptic targets of DA and glutamate release from dopaminergic neurons. Indeed, our biotinylation data addressing EAAT3(+) processes in slices more rostral to the midbrain suggests that AMPH-mediated endocytosis also occurs in terminal fields of DA projections (Figure S2C).…”
Section: Discussionmentioning
confidence: 93%
“…Although DA itself is clearly important for these actions, recent work underscores the importance of changes in glutamatergic signaling after AMPH treatment as well (Reissner and Kalivas, 2010; Wolf and Ferrario, 2010). For example, AMPH increases extracellular glutamate in various brain regions including the striatum, VTA and NAc (Del Arco et al, 1999; Kim et al, 1981; Mora and Porras, 1993; Xue et al, 1996), but it has not been established whether this change can be explained by increased synaptic release or by reduced clearance of glutamate. In vivo microdialysis studies indicate that the increases in extracellular glutamate are calcium independent (Del Arco et al, 1999; Del Arco et al, 1998; Xue et al, 1996) suggesting that synaptic release does not fully account for the observed increases in extracellular glutamate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Possibilities include dopamine, other monoamines such as norepinephrine and serotonin, glutamate, or even neuropeptides. AMPH-mediated release of some substances in rat striatum, such as glutamate (Mora and Porras, 1993), is mediated by released DA. Our studies with DA antagonists suggest that DA may not mediating the increases in synapsin or NM phosphorylation, although there was some effect of the D1 antagonist SCH23390 on synapsin I phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Small, clear vesicles and synapsin I are prominent in glutamatergic synaptosomes (Verhage et al, 1994). There appear to be interactions between dopaminergic and glutamatergic nerve terminals in striatum in that glutamate and DA may alter each other's release (Maura et al, 1988;Mora and Porras, 1993; and see references in Finnegan and Taraska, 1996). Low concentrations of DA suppressed the K 1 -induced release of glutamate in a presynaptic-inhibitory manner through dopamine D2 receptors on glutaminergic terminals innervated from cerebral cortex (Maura et al, 1988).…”
Section: Discussionmentioning
confidence: 99%